Enabling On-Device Inference of Large Language Models : Challenges, Techniques, and Applications - Athul Ramkumar (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This comprehensive article explores the cutting-edge techniques and challenges associated with on-device inference of Large Language Models (LLMs), a transformative approach that brings advanced AI capabilities directly to mobile and edge devices. The article delves into the intricate balance between the computational demands of LLMs and the resource constraints of mobile hardware, presenting a detailed analysis of various strategies to overcome these limitations. Key areas of focus include model compression techniques such as pruning and knowledge distillation, quantization methods, and the development of efficient model architectures. The article also examines the role of specialized hardware accelerators, including Neural Processing Units (NPUs), FPGAs, and ASICs, in enhancing on-device performance. Additionally, the article addresses critical aspects of memory management and optimization strategies crucial for efficient LLM deployment. Through a rigorous evaluation of performance metrics, the article offers insights into the trade-offs between model size, inference speed, and accuracy. It further explores diverse applications and use cases, from real-time language translation to privacy-preserving text analysis, highlighting the transformative potential of on-device LLM inference. The article concludes with an examination of ongoing challenges and future research directions, including improving energy efficiency, enhancing model adaptability, and addressing privacy and security concerns. This comprehensive article provides researchers, developers, and industry professionals with a thorough understanding of the current state and future prospects of on-device LLM inference, underlining its significance in shaping the next generation of AI-powered mobile and IoT applications.